Konseling Individu Dengan Teknik Self-Control Dalam Mengatasi Perilaku Narsisme Remaja Pengguna Tik-Tok Konseli “C” Di Kelurahan Baturaja Permai - Oktivioni, Frisky; Razzaq, Abdur; Jannati, Zhila (CV. ITTC INDONESIA, 2022)
The background of this research is that adolescents who experience narcissistic behavior tend to think excessively of themselves, thereby disturbing the environment and making themselves feel elated. The purpose of this study was to find out the description of narcissistic behavior of adolescents